PENGARUH BUDAYA ORGANISASI, KOMPETENSI APARATUR DESA DAN INTEGRITAS APARATUR TERHADAP PENCEGAHAN FRAUD YANG TERJADI DALAM PENGELOLAAN ALOKASI DANA DESA - I Gusti Ayu Agung Trisna Widyani; Ni Wayan Alit Erlina Wati (UNHI Press, 2020)
The purpose of this research is whether the organizational culture, the competence of the apparatus of desai and the integrity of the apparatus have an effect on the prevention of fraudi that occurs in managing the allocation of desai funds in the administration of the village of Blahbatuh. The object of this research is all the desai offices in the Blahbatuh district. In this research, a purposive sampling method was chosen with a total sample of 72 apparatus. The data analysis techniques used in this research are descriptive statistics, validation test, reliability test, classical assumption test, multiple linear regression, determination coefficient, F test and t test. The results of this research show that organizational culture has a positive influence on the prevention of fraudi with a positive coefficient of 0.183 with a significance value of 0.008 <0.05. This means that it supports a culture of organization and prevention of fraudi and increases this level. Apparatus competency has a positive effect on the prevention of fraudi with a positive coefficient of value of 0.466 with a significance value of 0.001 <0.05. This means that the competence of the apparatus is better and the prevention of fraudi will increase. Apparatus integration has a positive effect on the prevention of fraudi with a positive coefficient value of 0.221 with a significance value of 0.042 <0.05. This means that the stronger the integration then the prevention will be the better.